A little-known effort in the history of the wart: Dr. Ricardo Espinal - Lastres, Juan B. (1959)
The name of Ricardo Espinal, distinguished Venezuelan doctor, takes place of prominence in the history of the wart, because eb became clear the intricate set of symptoms of the disease, sitting for the first time and with masterly judgment, the etiologic eruptive unit wart and severe La Oroya fever.